Economic Independence Improvement of Melati MSMEs in Kedungbenda Village Through the Use of Production Technology and Digital Branding - Famila Dwi Winati; Gladi Pawestri Utami; Diovianto Putra Rakhmadani; Juni Aditya Hidayatullah; Rizq Athallah Puddin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Melati MSME is located in Kedungbenda Village, Purbalingga and faces several challenges in improving the quality and quantity of production and expanding market share. This is due to the need for digital literacy and UMKM Melati's ability to utilize production technology to support daily business. Therefore, this community service aims to encourage an increase in the economic independence of Melati MSMEs through the implementation of production technology and digital media. This program is carried out in several stages, starting from socialization, application of technology and innovation, training, mentoring, and evaluation. The production technology used is a cutting machine, spinner, and sealer to increase efficiency and product consistency. In addition, digital literacy was also improved through training on the use of social media and e-commerce for marketing, as well as the development of a visual identity in the form of a logo as a branding strategy. The results show an increase in the quality and quantity of Melati MSME production, as well as ease of market access using digital media. The program performance assessment showed significant success, with an average achievement of 95.71%. The increased ability of MSME members to use digital production and marketing technology contributed to the increase in turnover and production time efficiency. The program evaluation showed a high level of participant satisfaction, especially in terms of the benefits provided by this service activity. Through this program, Melati MSMEs can continue to develop and be economically independent by optimizing production technology and more effective digital marketing strategies.